Pengaruh Prinsip-Prinsip Good Corporate Governance dan Pertumbuhan Aset pada Kinerja Keuangan - Aget Luwih, Ni Made; Muliartha RM, Ketut (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p13, 2018)
This study aims to determine the effect of the principles of good corporate governance on financial performance as measured by the return on assets of cooperatives in the District of South Denpasar. This study uses data collection methods with questionnaire and documentation techniques. The sample used was 60 samples from 20 observing cooperatives in the District of South Denpasar and each of the three cooperatives was taken. The sample determination method uses purposive sampling. The analysis technique used is multiple linear regression analysis with SPSS. Based on the results of testing the hypothesis shows, responsibility principle. negative effect on the cooperative's financial performance, while the principles of transparency, accountability, independence, fairness and asset growth have no significant effect on the cooperative's financial performance in the District of South Denpasar. Keywords: good corporate governance, asset growth, cooperatives, financial performance, return on assets.